2018
DOI: 10.1177/2474126418764977
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Shape of Foveal Avascular Zone by Optical Coherence Tomography Angiography in Eyes With Branch Retinal Vein Occlusion

Abstract: To determine the relationship between morphological parameters of the foveal avascular zone (FAZ) in the optical coherence tomography angiographic (OCTA) images and the best-corrected visual acuity (BCVA) in branch retinal vein occlusion (BRVO). Methods: This was a retrospective cross-sectional study. Eyes with BRVO without apparent macular edema were studied. The superficial FAZ in 3 Â 3 mm OCTA images were delineated manually. The size and shape, the circularity and axial ratio, of the FAZ were determined, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 40 publications
(63 reference statements)
0
7
1
Order By: Relevance
“…OCT angiography (OCTA) is a new imaging technology that can obtain the images of the retinal vasculature non-invasively. The foveal avascular zone (FAZ) is a circular area with a diameter of 500 µm where the retinal capillaries are absent 11 , 12 . The clinical value of FAZ on OCTA has been extensively explored in many retinal diseases 11 15 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…OCT angiography (OCTA) is a new imaging technology that can obtain the images of the retinal vasculature non-invasively. The foveal avascular zone (FAZ) is a circular area with a diameter of 500 µm where the retinal capillaries are absent 11 , 12 . The clinical value of FAZ on OCTA has been extensively explored in many retinal diseases 11 15 .…”
Section: Introductionmentioning
confidence: 99%
“…The foveal avascular zone (FAZ) is a circular area with a diameter of 500 µm where the retinal capillaries are absent 11 , 12 . The clinical value of FAZ on OCTA has been extensively explored in many retinal diseases 11 15 . There are several reports on FAZ in ERM 16 19 .…”
Section: Introductionmentioning
confidence: 99%
“…The indices chosen to characterize the FAZ geometry were area, axial ratio, circularity, and roundness. 23,25 Circularity is a shape descriptor that can mathematically indicate the degree of similarity of the FAZ to a perfect circle. A value of 1.0 designates a perfect circle; thus, as the circularity value decreases, the shape is increasingly less circular.…”
Section: Geometric/morphologic Parameters Of the Foveal Avascular Zonementioning
confidence: 99%
“…The use of FAZ area as a biomarker for retinal diseases has been extensively studied in the literature. [21][22][23] However, measurements of even normal FAZ size can have large intersubject variability that correlates with a patient's age, sex, axial length, refractive error, and central macular thickness. 24 Foveal avascular zone geometry has been demonstrated to display good reproducibility and repeatability in normal subjects, possibly being a more reliable tool to detect vascular alterations when evaluating the SCP.…”
mentioning
confidence: 99%
“…Using OCTA, Shiihara et al [129] studied the relationship between morphological parameters (axial ratio and acircularity index) of the FAZ and BCVA in eyes with BRVO. Results demonstrated that acirculatory index is not significantly correlated to BCVA in RVO.…”
Section: Retinal Vein Occlusionmentioning
confidence: 99%